Tinea capitis in the form of concentric rings in an HIV positive adult on antiretroviral treatment - Kirti Narang; Manish Pahwa; V Ramesh (Wolters Kluwer Medknow Publications, 2012)
Dermatophyte infection may present in the form of concentric rings caused by Trichophyton concentricum, known as Tinea Imbricata. In immunosuppressed patients, there are reports of lesions in the form of concentric rings caused by dermatophytes other than Trichophyton concentricum too, mostly by Trichophyton tonsurans, known as Tinea indesiciva or Tinea pseudoimbricata. We report a case of tinea capitis in a HIV-positive adult woman on antiretroviral therapy, who presented with concentric rings of papules and pustules with slight scaling on the scalp along with diffuse thinning of hair. Both Potassium hydroxide mount and culture showed the presence of Dermatophytes. Tinea capitis is considered rare in adults, but new cases are being reported in immunocompromised as well as in immunocompetent patients. The pertinent features of this case are: HIV-positive adult female on antiretroviral therapy, presenting with tinea capitis in the form of concentric rings; culture from the lesion grew Microsporum audouinii; responding to oral Terbinafine.